PERSONALIZED LEARNING THROUGH ARTIFICIAL INTELLIGENCE IN ENGLISH LANGUAGE EDUCATION - Hojiakbar Akhmadjonov (Ta’lim innovatsiyasi va integratsiyasi, 2026)
Abstract. Artificial Intelligence (AI) has transformed modern education by enabling personalized learning experiences that meet the diverse needs of individual students. In English language education, AI-powered technologies provide adaptive instruction, instant feedback, personalized learning paths, and interactive learning environments that improve students’ language proficiency and motivation. Unlike traditional classroom instruction, where all learners often receive the same materials and pace of instruction, AI allows educational content to be tailored according to students’ abilities, learning styles, and progress. This article explores the role of artificial intelligence in personalized English language learning, discusses its advantages and challenges, and highlights practical applications of AI in English language education.